2018
DOI: 10.1097/scs.0000000000004607
|View full text |Cite
|
Sign up to set email alerts
|

Growth Factors Release From Concentrated Growth Factors: Effect of β-Tricalcium Phosphate Addition

Abstract: The present data suggest that β-TCP addition to CGF could enhance and improve tissue regeneration, especially bone regeneration, increasing the release of some growth factors that play an important role in osteogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 50 publications
1
14
0
2
Order By: Relevance
“…In the present study, a slow release of BMP-2 was detected during at least 7 days in both L-PRF and CGF, even if the quantities remained quite small. It is interesting to notice that small quantities of BMP-2 has also been detected in L-PRF (Dohan Ehrenfest et al, 2018) and CGF (Bonazza et al, 2018) in previous publications. It has been reported that the different cell populations (mostly leukocytes) living in the fibrin clot may contribute to the release of BMP-2 (Dohan Ehrenfest et al, 2018).…”
Section: Discussionmentioning
confidence: 65%
“…In the present study, a slow release of BMP-2 was detected during at least 7 days in both L-PRF and CGF, even if the quantities remained quite small. It is interesting to notice that small quantities of BMP-2 has also been detected in L-PRF (Dohan Ehrenfest et al, 2018) and CGF (Bonazza et al, 2018) in previous publications. It has been reported that the different cell populations (mostly leukocytes) living in the fibrin clot may contribute to the release of BMP-2 (Dohan Ehrenfest et al, 2018).…”
Section: Discussionmentioning
confidence: 65%
“…Architecture and components of different scaffolds may provide more interface area for release or affect its cell attachment (Yu et al, ). Bonazza et al showed that the mixture of CGFs with β‐TCP could increase the release of BMP‐2 and BMP‐7 due to the presence of Ca ions in β‐TCP (Bonazza et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a study on the release pattern of CGF in scaffolds, like deproteinized bovine bone mineral and intrafibrillar‐mineralized collagen (IMC), showed that mixture of CGF with IMC causes a sustained release of growth factors and cytokines until 28 days (Yu, Wang, Liu, & Qiao, ). It seems that addition of some biomaterials—like beta‐tricalcium phosphate (β‐TCP)—could enhance the release of some growth factors, like bone morphogenetic protein (BMP) 2 and 7, which have an important role in bone regeneration (Bonazza et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Cihaz içindeki kan tüpleri 30 saniye hızlanma, 2 dakika 2700 rpm (600 g), 4 dakika 2400 rpm (400 g), 4 dakika 2700 rpm (600 g), 3 dakika 3000 rpm ve 36 saniye yavaşlama içeren bir programla çalışıldı. İşlem sonunda 3 farklı kan fraksiyonu tanımlandı; 1) en üstte sıvı yapıda trombositten fakir plazma (PPP), 2) ortada daha katı kıvamda CGF, 3) en altta ise kırmızı kan hücrelerinden oluşan tabaka (12). Alınan orta CGF tabakası özel bir maşa yardımı ile sıkıştırılarak ince bir CGF matriks elde edildi (Şekil 1).…”
Section: Konsantre Büyüme Faktörü Hazırlanmasıunclassified
“…Fibroblast büyüme faktörü (FGF) granülasyon doku formasyonunda, reepitelizasyonda ve doku yeniden şekillendirilmesinde rol alır (1). İnsülin benzeri büyüme faktörü 1 (IGF-1), hücre apopitozunu geciktirir ve IGF-1 reseptörü endotelial cevapta önemli rol alır (12). Granüller içinde ayrıca trombosit kaynaklı anjiogenez faktörü (PDAF), trombosit faktör 4 (PF-4), keratinosit büyüme faktörü (KGF) ve interlökin 1 (IL-1) bulunmaktadır (8,11).…”
Section: Introductionunclassified